SUITABILITY ASSESSMENT OF ORANGE FLESHED SWEETPOTATO VARIETIES AT NORTHERN REGION OF BANGLADESH - Hossain, M.M.; Heck, S.; Chanda, D.; Rahaman, E.H.M.S.; Uddin, S.; Hasan, M.M.; Kabir, M.H. (IJAEB Publication, 2020)
ABSTRACT The present experiment was conducted with four Bangladesh Agricultural Research Institute (BARI) released orange fleshed sweetpotato varieties and a local cultivar as check at Sadar Upazila of Gaibanda and Pirgachha Upazila of Rangpur district during 2019-20 cropping season for their suitability assessment. It was found that all yield and yield contributing characters varied significantly at both the locations. Due to higher adaptability in northern conditions, it was observed that the variety of BARI SP-12 produced the highest yield (39.63 ton/ha at Gaibandha and 30.02 t/ha at Rangpur) followed by BARI SP-8 (32.03 ton/ha at Gaibandha and 25.93 t/ha at Rangpur) while the lowest was recorded in BARI SP-15 (13.33 ton/ha at Gaibandha and 3.03 ton/ha at Rangpur). Considering locations, all the studied varieties performed better at Gaibandha than Rangpur district. The crop was evaluated at vegetative and harvesting stage at farmers’ field by the farmers, researchers and extension staffs. At harvesting stage evaluation results revealed that, BARI SP-8 ranked first at Gaibandha and BARI SP-12 at Rangpur while BARI SP-4 ranked (2nd) at both locations. During harvesting stage evaluation, participants preferred BARI SP-12 as at both locations followed by BARI SP-8 at Gaibandha and BARI SP-4 at Rangpur. Through organoleptic test BARI SP-4 and BARI SP-12 found good to excellent by the farmers, researchers and extension staffs. Keywords: Sweet potato, evaluation, organoleptic test.